EPIDEMIOLOGY OF ISCHEMIC STROKE IN UZBEKISTAN AS EXEMPLIFIED BY THE NEUROLOGICAL DEPARTMENT OF THE REPUBLICAN SCIENTIFIC CENTER FOR EMERGENCY MEDICINE - Bakhadirkhanov, M.M.; Nazarova, Zh.A.; Rakhmatova, S.N.; Abdurakhmonova, K.B. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: Analysis of the frequency of occurrence of various types of strokes and study of data on the epidemiology of subtypes of ischemic stroke (II). Material and methods: The hospitalization of patients with AI in the neurological department of the Republican Scientific Center for Emergency Medicine in 2017-2019 was analyzed. In total, 2366 patients turned to the department with cerebrovascular accidents. The most common AI was 1540 (65.1%) patients, the second place was hemorrhagic stroke – 518 (21.9%) patients, the third – CIM – 308 (13%) patients. Results: The most common was the atherothrombotic type of ischemic stroke, the least common was the hemodynamic type. Persons with hypertension who use tobacco and are overweight have the highest risk of ischemic stroke of various types; the probability of occurrence of ischemic stroke is higher in autumn and spring. Conclusions: The highest risk of various types of AI occurring is for people with hypertension, both mono-disease, and in combination with atherosclerosis, who use tobacco and are overweight, the likelihood of occurrence of AI increases in autumn and spring. Given this, preventive measures should be carried out most carefully in the beginning of autumn and at the end of winter, paying particular attention to smoking patients who are overweight and hypertensive in various combinations with another pathology.